2022
DOI: 10.48550/arxiv.2205.02137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial search by continuous-time quantum walks on renormalized Internet networks

Abstract: We study spatial search with continuous-time quantum walks on real complex networks. We use smaller replicas of the Internet network obtained with a recent geometric renormalization method introduced by García- Pérez et al. (2018). This allows us to infer for the first time the behavior of a quantum spatial search algorithm on a real complex network. By simulating numerically the dynamics and optimizing the coupling parameter, we study the optimality of the algorithm and its scaling with the size of the networ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Childs and Goldstone [13] found that the spatial search problem for the complete graph, the hypercube graph, and d-dimensional periodic lattices of d > 4 can be solved in optimal time using continuous-time quantum walks. A number of high dimensional graphs were subsequently found that permit optimal spatial search [14][15][16][17][18][19][20][21][22][23]. Recently, optimal spatial search in one dimension using long-range interactions was found to be possible [24].…”
Section: Introductionmentioning
confidence: 99%
“…Childs and Goldstone [13] found that the spatial search problem for the complete graph, the hypercube graph, and d-dimensional periodic lattices of d > 4 can be solved in optimal time using continuous-time quantum walks. A number of high dimensional graphs were subsequently found that permit optimal spatial search [14][15][16][17][18][19][20][21][22][23]. Recently, optimal spatial search in one dimension using long-range interactions was found to be possible [24].…”
Section: Introductionmentioning
confidence: 99%